Enhancement of dissolution rate and hypoglycemic activity of glibenclamide with β-cyclodextrin - Jayachandra Babu R.; Pandit J.K. (My University, 2025)
Glibenclamide formed an inclusion complex with β-cyclodextrin in solution and in the solid state. Phase solubility studies revealed a three-fold increase in the solubility of glibenclamide in the presence of β-cyclodextrin. The formation of an inclusion complex with β-cyclodextrin in the solid state was confirmed by infrared spectroscopy, X-ray diffractometry and differential scanning calorimetry. The in vitro dissolution rates of glibenclamide/β-cyclodextrin inclusion complex and a kneaded mixture were respectively eight and seven times higher at 20 min than the pure drug. Oral administration of the inclusion complex and the kneaded mixture to diabetic rats at 1 mg glibenclamide equivalent/kg dose level significantly lowered blood glucose levels at 4 h (p < 0.02) and at 6 and 8 h (p < 0.05), as compared with the same dose level of pure glibenclamide. In contrast, at 0.7 mg glibenclamide equivalent/kg dose level, the inclusion complex at kneaded mixture produced a similar hypoglycemic effect as that of 1 mg/kg of pure glibenclamide.